2006
DOI: 10.12968/ijpn.2006.12.4.21010
|View full text |Cite
|
Sign up to set email alerts
|

Caring for patients with terminal delirium: palliative care unit and home care nurses’ experiences

Abstract: Findings suggest the need for interdisciplinary educational initiatives focused on the identification and management of terminal delirium, and targeted to the specific context in which nurses practise.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
47
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(48 citation statements)
references
References 20 publications
1
47
0
Order By: Relevance
“…In the study by Brajtman et al (2006), palliative care nurses caring for patients with terminal delirium ( n = 10) reported that the discomfort they felt was due above all to the distress they perceived in the persons affected by delirium and in their families. For participants ( n = 10) in the study by Stenwall et al (2007), instead, discomfort was caused, in particular, by the complex situations in which they had to take into account various constraints that rendered the decision‐making process difficult.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the study by Brajtman et al (2006), palliative care nurses caring for patients with terminal delirium ( n = 10) reported that the discomfort they felt was due above all to the distress they perceived in the persons affected by delirium and in their families. For participants ( n = 10) in the study by Stenwall et al (2007), instead, discomfort was caused, in particular, by the complex situations in which they had to take into account various constraints that rendered the decision‐making process difficult.…”
Section: Resultsmentioning
confidence: 99%
“…For their part, participants ( n = 5) in the study by Lou and Dai (2002) explained that they sought to balance the unexpected situation with their workload by getting families involved in supervising patients and ensuring their safety, by communicating with physicians and by seeking support from their peers. As for participants ( n = 10) in the study by Brajtman et al (2006), they indicated that their presence and continuity of care helped calm and support persons in delirium and their families and added that they needed the professional and non‐professional interdisciplinary team and better knowledge of delirium to offer quality care.…”
Section: Resultsmentioning
confidence: 99%
“…9 A study of palliative care nurses described witnessing the distress experienced by these patients, and their loved ones; and the difficulty in achieving a peaceful death. 25 It is important that we consider this impact when we are planning care in our multidisciplinary teams and in the support mechanisms put in place.…”
Section: Discussionmentioning
confidence: 99%
“…7,9,25,26 These studies have identified that the care of the confused patient is often stressful and distressing, with highly variable assessment and management strategies. 7,9,25,26 Focus of care was often on 'controlling the situation', keeping an eye on the patient and reliance on behavioural symptoms as a clue for delirium. 7,26 The experiences of nurses in oncology, geriatrics or geriatric psychiatry settings have not been compared directly before.…”
mentioning
confidence: 99%
“…19 The sample included five nurses working in an interdisciplinary palliative care unit in a large Canadian city hospital and four nurses from a palliative home-care nursing team in the same city. Results indicated that nurses in both sites experienced multiple challenges in caring for delirious patients.…”
Section: Literature Reviewmentioning
confidence: 99%